Glacial-interglacial changes in equatorial Pacific surface-water structure during the Plio-Pleistocene intensification of Northern Hemisphere Glaciation - Jakob, Kim; Bahr, André; Pross, Jörg; Friedrich, Oliver (Earth and planetary science letters, 2017)
The late Pliocene/early Pleistocene intensification of Northern Hemisphere Glaciation (iNHG) represents the most recent major tipping point in Earth's climate history. In the equatorial Pacific, the iNHG has been suggested to mark the transition from a warm Pliocene climate state, in which the Pacific warm pool was greatly expanded relative to today giving rise to a surface ocean temperature field akin to modern El Niño conditions, to a climate state with strong upwelling in the east of the basin and stronger zonal temperature gradients. Here we examine this transition by presenting new high-resolution (∼800 yr) planktic foraminiferal Mg/Ca- and δ 18 O-based sea-surface temperature (SST) and salinity (SSS; based on δ 18 O residuals [ δ 18 O ivc-sw ]) records from Eastern Equatorial Pacific (EEP) Ocean Drilling Program Site 849 spanning ∼2.75-2.4 Ma. Our study interval contains the first large-amplitude (∼1‰ in benthic δ 18 O) early Pleistocene glacial-interglacial cycles (Marine Isotope Stages 100-96) representing the culmination of iNHG. In this study we investigate west-to-east equatorial Pacific SST and SSS gradients. We find that the zonal SST gradient increased by ∼1.5 °C from ∼2.75 to ∼2.4 Ma through EEP cooling. No glacial-interglacial pattern is seen in this gradient. On the other hand, we document obliquity-paced oscillations in the δ 18 O ivc-sw (SSS) gradient. We hypothesize that these oscillations originated from a response to a glacial southward and interglacial northward migration of the Intertropical Convergence Zone over the EEP.
Gesehen am 06.07.2017